Localization and survival of Azospirillum brasilense Az39 in soybean leaves - Puente, Mariana Laura; Maroniche, Guillermo Andrés; Panepucci, Marina Gabriela; Sabio Y Garcia, Julia Veronica; García, Julia Elena; Criado, María Victoria; Molina, Romina Micaela; Cassán, Fabricio Dario (Wiley, 2021)
In recent years, foliar inoculation has gained acceptance among the available methods to deliver plant beneficial micro-organisms to crops under field conditions. Colonization efficiency by such micro-organisms largely depends on their ability to survive when applied on the leaves. In this work, we evaluated the survival and localization of Azospirillum brasilense Az39 (Az39) in excised soybean leaves. Scanning electron microscopy and confocal laser scanning microscopy of a red fluorescent-transformed variant of Az39 were used to determine bacterial localization, while the most probable number and plate count methods were applied for bacterial quantification. Microscopic observations indicated a decrease in the number of Az39 cells on the leaf surface at 24 h after treatment, whereas midribs and cell–cell junctions of the inner leaf epidermis became highly populated zones. The presence of Az39 inside xylem vessels was corroborated at 6 h after bacterization. Az39 population did not significantly decrease throughout 24 h. We could visualize Az39 cells on the surface and in internal tissues of soybean leaves and recover them through culture methodologies. These results evidence the survival capacity of Az39 on and inside leaves and suggest a previously unnoticed endophytic potential for this well-known plant growth-promoting rhizobacteria strain.